2018
DOI: 10.15420/ecr.2017:20:3
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Implications of Sphingomyelin Presence in Biological Membranes

Abstract: Sphingomyelin (SM) is a type of sphingolipid found within plasma, cellular membranes and plasma lipoproteins. Here we highlight the basic biochemical features of SMs and their role in biological membranes. We further discuss evidence of the association between SM and cardiovascular diseases such as atherosclerosis, valvular disease, heart failure and diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Disruption of SM homeostasis has been also linked to an adverse cardiovascular outcome [17]. Recent studies have demonstrated a positive correlation between serum SM levels and insulin resistance and inflammation [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of SM homeostasis has been also linked to an adverse cardiovascular outcome [17]. Recent studies have demonstrated a positive correlation between serum SM levels and insulin resistance and inflammation [50].…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomyelin (SM), complex sphingolipid found in plasma and cellular membranes, plays a pivotal role in membrane stability and cell cholesterol homeostasis [16]. Several studies demonstrated an association between altered SM levels and cardiovascular diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple in vitro studies observed upregulation of aSMase and nSMase along with increased SM in animal models of HF ( 125 , 126 ). The nSMase and aSMase hydrolyze sphingomyelin to release ceramide, and thus the accumulation of ceramide in post-ischemic heart may arise from SM catabolism and not de novo sphingolipid biosynthesis ( 127 , 128 ). Another study in both mice and humans with HF noted increased levels of SPTLC2, which participates in de novo sphingolipid synthesis and likely contributes to the significant increase of total ceramides in the aforementioned studies ( 45 ).…”
Section: Sphingolipids In Cardiovascular Diseasementioning
confidence: 99%
“…Triacylglycerols and phospholipids featuring both polar and non-polar regions are common in mammalian cell membranes. Sphingomyelins, a type of sphingolipid, are important components of the membranes of nerve axons that promote nerve conduction [4]. Other fatty acids are stored as non-polar triacylglycerols and sterol esters in intracellular lipid droplets that function as long-term energy reservoirs and as a stockpile of fatty acids and sterols needed for membrane biosynthesis [5].…”
Section: Lipids In Farmed Animal Tissues Eggs Milk and Fishmentioning
confidence: 99%